Altered Metabolomics in Bipolar Depression With Gastrointestinal Symptoms - Guo, Xiang-Jie; Xiong, Yan-Bing; Jia, Yuan; Cui, Xiao-Hong; Wu, Wen-Ze; Tian, Jun-Sheng; Yang, Hong; Ren, Yan (Frontiers in Psychiatry, 2022)
Objective: Although gastrointestinal (GI) symptoms are very common in patients with bipolar disorder (BD), few studies have investigated the pathomechanism behind these symptoms. In this study, we sought to elucidate the pathomechanism of GI symptoms in BD by metabolomic analysis. Method: BD patients were recruited from Shanxi Bethune Hospital that categorized into two groups, each of which is based on the presence or absence of GI symptoms evaluation with the 24-item Hamilton Depression Rating Scale (HAMD-24). Healthy controls were recruited from the medical examination center of the same hospital. Differential metabolites were identified and further analyzed using Metabo Analyst 3.0 to identify associated metabolic pathways. Results: There were significantly higher HAMD-24 scores in the GI symptoms group than that of non-GI symptoms group (p = 0.007). Based on metabolomic analysis results, we found that the common disturbances metabolic pathway of both two patients groups was ketone body metabolism, and the unique disturbances metabolic pathways of BD with GI symptoms were fatty acid biosynthesis and tyrosine metabolism, and these changes were independent of dietary habits. Conclusion: BD patients with GI symptoms exhibited disturbances in fatty acid and tyrosine metabolism, perhaps suggesting that the GI symptoms in BD patients are related to disturbances of the gut microbiome. Both patients groups together exhibit disturbances in the ketone body metabolism, which may serve as a biomarker for the pathogenesis of BD patients.